Enhanced mechanical and thermal properties of nanodiamond reinforced low density polyethylene nanocomposites. Issue 37 (28th April 2021) - Morimune‐Moriya, Seira; Hashimoto, Taiki; Haga, Ryohei; Tanahashi, Hiroaki
Abstract: In this study, the reinforcement effects of low‐content hydrophilic nanodiamond (ND) on linear low‐density polyethylene (PE) nanocomposites were investigated. ND was incorporated in PE via simple solution blending. The obtained PE/ND nanocomposites were characterized using scanning electron microscopy, ultraviolet–visible spectra, X‐ray diffraction, tensile test, thermogravimetry, and differential scanning calorimetry. Generally, PE/ND nanocomposites with poor interfacial interaction cause large agglomerates, resulting in brittle and poor mechanical properties. Owing to the different natures of non‐polar PE and polar ND, the higher the ND content, the larger the agglomerates formed in the nanocomposites. However, PE/ND nanocomposites show unique mechanical properties, that is, the Young's modulus, tensile strength, elongation at break, and toughness increased upon the incorporation of ND. The Young's modulus of the PE/ND nanocomposites exceeded the theoretical value calculated using the Halpin–Tsai model. In addition, the toughness increased by 18% at only 0.5 wt% ND loading. Furthermore, there was an increase in the thermal degradation temperature, melting temperature, and crystallization temperature. Abstract : The remarkable enhancements in the mechanical properties and thermal properties of the linear low‐density polyethylene nanocomposites were achieved by the incorporation of nanodiamond. For example, the Young's modulus of the nanocomposites exceeded the theoretical values. In the present study, the detailed structure and properties of polyethylene/nanodiamond nanocomposites were investigated.